FUNDAMENTALS OF INTEGRATED COMMERCIAL BANK IN MACROECONOMIC AND SHARIA PERSPECTIVE IN INDONESIA - Jati, Kumara; Salam, Aziza Rahmaniar (Journal of Islamic Monetary Economics and Finance, 2018)
This research analyses the fundamentals of integrated commercial bank in macroeconomic and sharia perspective in Indonesia. Based on the calculation of Vector Autoregression (VAR), the impact of macroeconomic variables (Jakarta Stock Islamic Index / JKSII, Indonesian Stock Price Composite Index / JKSE, Crude Oil Price, and Exchange Rate) on stock prices of commercial banks vary. These shocks indicate an indirect price transmission through exchange rate channels and economic growth. From the Structrural Time Series Model (STSM), JKSII, JKSE, and commercial bank share price prediction will generally increase at the end of 2017 and 2018. This will generate hope and benefit for policy maker and business actors in the banking, finance and sharia sectors. In general, the ARMA-ARCH/GARCH model with dummy variables found negative impact of “Fasting Period and Eid Al-Fitr” on return of JKSII, JKSE, and commercial bank stock price. This indicates a cycle of stock price decline that occurs when consumers spend more money to purchase goods and services. However, this cycle of stock price declines is only temporary because the recovery of the world economy and the increase in demand for goods and services in the future can be a pull factor for stock prices (demand factor). Policy makers and stakeholders related to the financial system, banking and capital markets, especially the sharia sector need to see the movement of conventional bank stocks and “Fasting Period and Eid Al-Fitr” as they move in the opposite direction for a certain period.